Penguatan Komunikasi Organisasi Bagi Organisasi Dakwah Perempuan - Nur’aeni, Siti; Fauzia Hakim, Alfi; Fauzi Rahman, dkk, Mufti (E-Coops-Day, 2024)
This Community Service Program (PKM) aims to increase the knowledge of members of the Branch Leadership (PC) organization of the Rancaekek Islamic Association of Bandung Regency, especially in terms of strengthening communication for the organization. The program implementation method uses a Participatory Rural Appraisal (PRA) approach, involving four stages: To Know, To Understand, To Plan and To Act, with a focus on improving members' skills and communication. The program results showed an increase in participants' knowledge of communication skills in organizations. Before education, their average knowledge score was 55.60 with a total score of 278 points. After education, the average score increased to 78.40 with a total score of 392 points. This increase shows that this program makes a positive contribution in increasing the understanding, skills and commitment of organizational members, as well as creating a more dynamic and productive organizational atmosphere. The evaluation results also become the basis for further program improvements. This article can be a reference for researchers, practitioners and related parties in efforts to empower women in missionary organizations.